Oxidative Stress and Some Liver Functions Parameters in Patients with Symptomatic Cholelithiasis - Ridha, Nibrass M.; Taher, Mohammed A. (Journal of the Faculty of Medicine Baghdad, 2013)
Background : Gallstone disease is one of a common surgical problem and one of the most common gastrointestinal diseases throughout the world but its pathogenesis remains unclear. Many theories have been put forward to explain the mechanism of stone formation. The living organism has enzymatic and non-enzymatic antioxidant systems neutralizing the harmful effects of the endogenous oxygen free radicals products. Under certain conditions, the oxidative or anti-oxidative balance shifts towards the oxidative status as a result of increase in oxygen free radicals and/or impairment in antioxidant mechanism. Objective :To evaluate the oxidative stress markers (total antioxidants capacity and malondialdehyde) and some liver functions parameters (aspartate aminotransefrerase , alanin aminotranseferase , alkaline phosphatase , total serum bilirubin )in serum of patients with gallstone disease and in control group. Patients & Methods : The study group included 75 patient with gallstone disease and 33 age- and sex-matched healthy volunteers as control group. Antioxidative status of serum was evaluated by measuring total antioxidant capacity . serum: malondialdehde , aspartate aminotranseferase , alanine aminotransferase , alkaline phosphatase, and total bilirubin, were all measured in serum of patients with gallstones and controls. Results : There was a significant increase(P<0.05) in serum: malondialdehyde, alkaline phosphatase , alanin aminotranseferase ,aspartate aminotransefrerase , total serum bilirubin levels in patients with symtomatic gallstones compared to healthy controls. The study also showed that there was a significant decrease in serum total antioxidant capasity (P<0.05) in the patients compared to control group . Conclusion : The present study results indicated that patients with gallstones may have been exposed to oxidative stress . change in liver functions parameters was also seen in serum of patients compared to controls . these findings may provides insights and helps in understanding the various biochemical alterations undergoing in the gallbladder responsible for stone formation and would be helpful in developing strategies for the treatment and prevention of gallstones.